Perilaku Seksual Pranikah Berisiko Terhadap Kehamilan Tidak Diinginkan PadaRemaja SMKN Tandun Kabupaten Rokan Hulu - Wulandari, Sri (Jurnal Martenity and Neonatal, 2016)
Increasing premarital sexual behavior among college students today needs special attention from all parties, including the universities. The case of an unwanted pregnancy, abortion, and sexually transmitted infections premarital are more common among students. Research problem was whether the factors that influence the risk of premarital sexual behavior to unwanted pregnancy in college students. Research purpose was to determine the factors that influence to premarital sexual behavior to unwanted pregnancy in college students. Methods research was explanatory research with cross sectional approach. Sample was mostly students who totaled 380 students, by proportional simple random sampling. The results of this study showed that 12.1 % of students have high risk of premarital sexual behavior to unwanted pregnancy. Bivariate analysis by chi square test showed that religiosity; attitudes, access and contact with pornography media, close friend’s attitudes and sexual behavior were significantly associated with premarital sexual behavior of students. Conclusion, close friend’s sexual behavior, respondent’s sexuality attitudes, and religiosity dominant influence to sexual behavior for student’s unwanted pregnancy.